La inteligencia social y sus implicaciones en la evolución de la mente (2011)
ABSTRACT: This article discusses two theories about the evolution of the human mind, Calvin’s (1996, 2004) theory of the mental organization as a derivative product of the complex and changing environmental conditions, and Humpreys’s (1998, 2002) theory about the human mind and its characteristics as a consequence of adaptations to social environment. Both theories are supported by a strong empirical background that helps to develop and push further better research about the organization, evolution, and development of the mind.